The need for a behavioural analysis of behavioural addictions - James, Richard J.E.; Tunney, Richard J. (Elsevier, 2017)
This manuscript overviews the behavioural (i.e. associative learning, conditioning) research in behavioural addictions, with reference to contemporary models of substance addiction and ongoing controversies in the behavioural addictions literature. The role of behaviour has been well explored in substance addictions and gambling but this focus is often absent in other candidate behavioural addictions. In contrast, the standard approach to behavioural addictions has been to look at individual differences, psychopathologies and biases, often translating from pathological gambling indicators. An associative model presently captures the core elements of behavioural addiction included in the DSM (gambling) and identified for further consideration (internet gaming). Importantly, gambling has a schedule of reinforcement that shows similarities and differences from other addictions. While this is more likely than not applicable to internet gaming, it is less clear whether it is so for a number of candidate behavioural addictions. Adopting an associative perspective, this paper translates from gambling to video gaming, in light of the existing debates on this matter and the nature of the distinction between these behaviours. Finally, a framework for applying an associative model to behavioural addictions is outlined, and it's application toward treatment.